Decrease from main root canal and intratubular Fusobacterium nucleatum and its endotoxin after ultrasonic activation of conventional and alternative irrigation solutions - Barros, Mirela Cesar; Feliz Pedrinha, Victor; Eduardo Oliveira, Felipe [UNESP]; Marcucci, Maria Cristina [UNESP]; Gomes, Brenda Paula F. A.; Oliveira, Luciane Dias de [UNESP]; Andrade, Flaviana Bombarda de (Taylor & Francis, 2024)
This study evaluated conventional and alternative irrigation solutions combined with ultrasonic irrigant activation (UIA) against Fusobacterium nucleatum (F. nucleatum) and its endotoxin (LPS) in main root canal and dentinal tubules, using a new intratubular infection model. Seventy dentin cylinders were infected with F. nucleatum for seven days under anaerobic conditions and treated with 2.5% sodium hypochlorite (NaOCl), limewater + 2.5% NaOCl, and 10% ethanolic propolis extract (EEP), administered by syringe irrigation (SI) or UIA. Microbiological samples were collected before and after irrigation to determine CFU ml–1 and LPS levels. Confocal microscopy assessed bacterial membrane damage with Live/Dead staining. Irrigation solutions effectively reduced CFU ml–1. UIA caused greater damage to the bacterial membranes and reduced LPS levels. The ultrasonic activation of 10% EEP and limewater + 2.5% NaOCl were comparable to 2.5% NaOCl (p > 0.05). UIA improved the effectiveness of solutions, suggesting potential for alternative substances. Randomized clinical trials using these protocols are recommended.
Keywords: Endodontics; Fusobacterium nucleatum; microbiology; root canal irrigants; ultrasound